Kapabilitas Kepala Sekolah dalam Meningkatkan Disiplin Kerja Guru di SMP Islam Terpadu - Anhar, Anhar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Principals must have the capability to improve teacher performance. This study aims to explain and describe the Capability of the Principal in helping teachers to improve their quality and discipline at the Integrated Islamic Junior High School Nurul Khalifah Bima. This type of research is descriptive research with a qualitative approach. Data collection techniques in this study consisted of observation (observation), interviews (interviews), and documentation (documentation). The results showed, to improve teacher discipline in attendance, school principals also set good examples for teachers by attending school on time, optimizing disciplinary rules in attendance. In addition, the principal also tries to work collaboratively with the teachers by appointing teachers who he considers capable of supervising. The principal also coordinates with the picket officers who consist of 2 officers every day, namely from teachers who do not have teaching hours on that day and one person from administration. The picket officer will circulate the teacher attendance list in the class that has been made in order to see the level of teacher attendance in each class.